LLC Resonant Converter with Additional Secondary Winding to Extend Hold-Up Time. Issue 6 (3rd April 2017) - Lin, Bor-Ren; Du, Yan-Kang
Abstract: Resonant converters have been developed for commercial power units with the advantages of high circuit efficiency and high power density. However, the main drawback is the wide switching frequency variation. To solve this limitation, the auxiliary windings and switch are used in the proposed converter to provide a high voltage gain at low input voltage case when AC power is turned off. Therefore, the frequency variation is reduced compared to the conventional resonant converter. By using the auxiliary secondary windings, the hold-up time is extended to 40 ms (100% extension compared to the conventional hold-up time 20 ms). The operation principle, circuit characteristics, and design procedure of the adopted circuit are discussed in detail. Experimental verifications are provided to demonstrate the circuit performance.